Біологічно активні сполуки в харчових продуктах : методичні вказівки до практичних занять для здобувачів вищої освіти другого (магістерського) рівня денної форми здобуття освіти за спеціальністю 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» [Електронний ресурс] - Цихановська, Ірина Василівна; Александров, Олександр Валентинович; Кудін, Дмитро Костянтинович; Tsykhanovska, Iryna Vasylivna; Alexandrov, Alexander Valentinovich; Kudin, Dmitry Konstantinovich (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Методичні вказівки для здобувачів вищої освіти другого (магістерського) рівня денної форми здобуття освіти спеціальності 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» містять рекомендації щодо виконання практичних занять. Рекомендації складено відповідно до програми дисципліни «Біологічно активні сполуки в харчових продуктах», яка викладається магістрам 1 курсу спеціальності 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» ХНУ імені В.Н. Каразіна. Методичні вказівки допоможуть здобувачам вищої освіти засвоїти теоретичний курс і набути практичних навичок.

Methodological guidelines for higher education applicants of the second (master's) level of full-time education in the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» contain recommendations for conducting practical classes. The recommendations are compiled in accordance with the program of the discipline «Biologically active compounds in food products», which is taught to 1st year masters of the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» of the V.N. Karazin KhNU. Methodological guidelines will help higher education applicants master the theoretical course and acquire practical skills.
Biologically active compounds in food products : methodological instructions for practical classes for students of the second (master's) level of full-time higher education in the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» [Electronic resource]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; SOCIAL SCIENCES::Business and economics; NATURAL SCIENCES::Chemistry::Biochemistry; TECHNOLOGY::Chemical engineering::Food technology; TECHNOLOGY::Industrial engineering and economy::Manufacturing engineering and work sciences; TECHNOLOGY::Industrial engineering and economy::Industrial organisation, administration and economics; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Agricultural engineering; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area economics; INTERDISCIPLINARY RESEARCH AREAS::Domestic science and nutrition; біологічно активні сполуки; харчові продукти; biologically active compounds; food products